2019
DOI: 10.1163/15685381-20181048
|View full text |Cite
|
Sign up to set email alerts
|

Conspecifics of the Striped Lava Lizard are able to distinguish sex and male colour morphs in apparently homogeneous dull dorsal colouration

Abstract: Animal colouration plays a key role in inter and intraspecific interactions, pre-eminently in mate signalling. When multiple types of colouration occur within sexes it is possible that they show alternative reproductive strategies. In lizards, most colouration studies do not incorporate how colour is perceived by conspecifics. Here, we used unbiased colour analysis methods (spectrophotometry and visual modelling) to test for sexual dimorphism and within male dichromatism in the Striped Lava Lizard. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Melanistic coloured patches in the ventral thighs and pre‐cloacal flaps of adult males are diagnostic traits of the genus (Bruinjé, Coelho, et al, 2019; Bruinjé, Moura, et al, 2019; Ribeiro et al, 2012) but, to date, no chemical signalling function of these structures has been shown. Such patches can also be yellow coloured in T. semitaeniatus (Bruinjé, Coelho, et al, 2019; Bruinjé, Moura, et al, 2019), T. hispidus , T. oreadicus (A. C. Bruinjé, personal observation) and T. torquatus (Pinto et al, 2005). Pinto et al, (2005) reported ontogenetic changes in the colouration of femoral patches of T. torquatus , suggesting that patches were used in visual communication for sex recognition and hierarchy establishment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Melanistic coloured patches in the ventral thighs and pre‐cloacal flaps of adult males are diagnostic traits of the genus (Bruinjé, Coelho, et al, 2019; Bruinjé, Moura, et al, 2019; Ribeiro et al, 2012) but, to date, no chemical signalling function of these structures has been shown. Such patches can also be yellow coloured in T. semitaeniatus (Bruinjé, Coelho, et al, 2019; Bruinjé, Moura, et al, 2019), T. hispidus , T. oreadicus (A. C. Bruinjé, personal observation) and T. torquatus (Pinto et al, 2005). Pinto et al, (2005) reported ontogenetic changes in the colouration of femoral patches of T. torquatus , suggesting that patches were used in visual communication for sex recognition and hierarchy establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Such visual signalling could occur during the behaviour of lifting the body, which were reported for the species (Pinto et al, 2005). In addition, in T. semitaeniatus , ventral patches become more evident during the breeding season (Ribeiro, Kolodiuk, & Freire, 2010) and intensity of ventral patches’ colouration in males of this species are correlated to increased levels of aggression (Bruinjé, Coelho, et al, 2019; Bruinjé, Moura, et al, 2019). On the other hand, Harvey and Gutberlet (1998) described these patches as a diagnostic trait of the genus and proposed that its colouration results from the production and secretion of chemical compounds, thus suggesting that it is of little importance for visual signalling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). An exception is the striped lava lizard ( Tropidurus semitaeniatus ), in which males are either black or yellow (Bruinjé, Leivas, & Costa, 2018; Bruinjé et al ., 2019 b ). The Roze's gecko ( Gonatodes rozei ) also has strikingly different male morphs, with throats that are orange‐yellow, dull yellow, grey‐brown with pale yellow markings, or grey‐brown with black suffusions between yellow markings (Rivero‐Blanco & Schargel, 2012).…”
Section: Variation In Lizard Colour Polymorphismsmentioning
confidence: 99%